ERADICATING MOSQUITOES THAT CAUSE DENGUE FEVER IN KEDUNGJAYA VILLAGE THROUGH FOGGING IN KEDUNGJAYA VILLAGE, KEDAWUNG SUB-DISTRICT, CIREBON DISTRICT - Irawan Budi Utomo; Hartanto Halim; Ellin Herlina; Illa nuru Haidah; Aceng Abdul Hamid; Deviari D Soemarno; Vinny Meilinda Chandra; Assha Khomsiyah Dwiyani (Jurnal Abdisci, 2025)
Abstract Background. Dengue hemorrhagic fever (DHF) is an infectious disease caused by the dengue virus and transmitted through the bite of the Aedes aegypti mosquito. The spread of this disease can cause outbreaks in various regions, including Kedungjaya Village, Kedawung Subdistrict, Cirebon Regency. Aims. Effective handling of DHF requires continuous prevention efforts, one of which is through controlling the population of disease-causing mosquitoes. Methods. One method used to reduce mosquito populations is fogging or spraying insecticides. This study aims to analyze the effectiveness of fogging in eradicating mosquitoes that cause DHF in Kedungjaya Village. The method used was fogging, spraying insecticides on areas that become mosquito breeding grounds. Result. The results showed that fogging can significantly reduce mosquito populations, which in turn reduces the potential spread of DHF. To achieve optimal prevention, a comprehensive approach is needed, including educating the community on clean and healthy living behaviors and mosquito nest eradication efforts. Conclusion. This study is expected to contribute to DHF control efforts in the area and serve as a model for other regions facing similar problems. Implementation. Some suggestions that can be given to improve the effectiveness of DHF control in Kedungjaya Village